Multimodal interactive handwritten text transcription - Romero, Verónica; Romero, Verónica; Toselli, Alejandro Héctor; Vidal, Enrique (Series in machine perception and artificial intelligence, 2012)
This book presents an interactive multimodal approach for efficient transcription of handwritten text images. This approach, rather than full automation, assists the expert in the recognition and transcription process.